A Increased Motivation to Study Santri Through the Application of BCM (Playing Singing Stories) at Diniyah Takmiliyah Ula Darul Ulum Widang Tuban - Yuyun Bahtiar (JoEMS (Journal of Education and Management Studies), 2019)
Motivation and learning are two things that influence each other. Both are inseparable. Because learning without motivation will not achieve success. Motivation has an important role, because motivation provides a stimulus to students in learning, resulting in students' enthusiasm and feeling happy learning. Based on the above, the problem is formulated, namely (1) How is the concept of BCM in learning (2) How is the application of BCM in Diniyah Takmiliyah Ula Widang Tuban? (3) What is the impact of the application of BCM on students' learning motivation? The method used in this study uses qualitative methods as research procedures that produce descriptive data in the form of written or oral words from people and observed behavior. BCM is an effective method for increasing students' motivation to learn at Diniyah Takmiliyah Ula Widang, Tuban. In BCM ustadzah / ustadzah must pay attention to several things so that the BCM delivered can attract the attention of the santri. With good attention from the santri, the moral message conveyed by Ustadz / Ustadzah will be easily absorbed by every santri.